Prevention of Blackhole Attack over AODV and DSR MANET Routing Protocol (International Journal of Engineering and Computer Science, 2015)
Wireless technology is one of the biggest contributions to mankind. In wireless system, transmission of information can be done without the need of wires and cables. Mobile Adhoc Networks (MANETs) do not have any centralized administration. They are infrastructure-less networks. They do not contain any networking device like routers or access points. MANETs are self-starting and dynamicnetwork comprising of mobile nodes. Mobile Ad-hoc networks require routing protocols for communication among nodes. Due to the lack of centralized management, various attacks are possible in MANETs such as passive or active attacks. Blackhole attack is an active kind of attack in which a malicious node pretendsto have a shortest and fresh path to the destination. Blackhole attack affects the performance by disrupting the normal communication in the network. Therefore, there is need to prevent the network from attack. In this paper, prevention of blackhole attack is done over AODV and DSR routing protocol with Random Waypoint Model. Malicious nodes in the network are known and if malicious nodes encounter in between the route from source to destination, then intermediate node have to simply discard that path and have to find an alternate path.The simulation results show that AODV routing protocol performs best and is suitable for highly dynamic networks.